SINTESIS FASA ɣ-Co PADA PADUAN Co26Cr6Mo0.18N DENGAN KOMBINASI METODE HOMOGENISASI 1200 oC DAN HOT ROLLING SERTA TRANSFORMASI STRUKTUR KRISTALNYA - R. Ibrahim Purawiardi; I Nyoman G. P Astawa; Fendy Rokhmanto; Ika Kartika (University of Muhammadiyah Jakarta, 2018)
Co-Cr-Mo alloy is a material that widely used for bioimplant in the medical field due to its corrosion resistance and mechanical properties. Structurally, recommended Co-Cr-Mo alloys for medical applications are ɣ-Co phase which has an FCC structure. But, Co7Mo6 metastable phase often occurs after its synthesis. The formation of Co7Mo6 phase will decrease the composition of ɣ-Co phase. This study aimed to synthesize ɣ-Co phase without following the appearance of Co7Mo6 phase using a combination of 1200 oC homogenization and hot rolling followed by cooling treatment. The alloy used was Co26Cr6Mo0.18N ingot. Cooling treatments were done using the variation of cold water, water and air. The transformation of the crystal structure from the primitive cubic to the FCC occurs during water and air cooling treatments which means that ɣ-Co phase is successfully formed by those cooling treatments. However, Co7Mo6 phase is still formed on the water cooling treatment while none of Co7Mo6occurred on the air cooling treatment. Structurally, air cooling treatment produces most stable ɣ-Co phase than the others. However, brittle ɛ-Co phase as a partial dislocation is formed after air cooling treatment due to imperfection of hot rolling treatment.